KESADARAN WAJIB PAJAK DAN PERSEPSI KEMUDAHAN PENGGUNAAN E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK - Krisna Hari, Kurnia; Kusumawaty, Mia (Balance : Jurnal Akuntansi dan Bisnis, 2023)
This study aims to determine the effect of taxpayer awareness and perceived ease of use of e-Filling on taxpayer compliance. The type of research used in this research is associative research. The population in this study were 5,142 MSME taxpayers registered at KPP Pratama Seberang Ulu Palembang with 100 random samples. The data used is Primary Data. The method of collecting data in this study is using interviews, questionnaires, and documentation. The data analysis method used is descriptive statistical analysis method, classical assumption test and multiple linear regression, as well as data processing in this study using the IBM Statistical Program For Social Science (SPSS) version 16 computer program. The results of this study can be concluded that partially there the influence between taxpayer awareness and perceived ease of use of e-Filling on Taxpayer Compliance.